Co-inoculation of fungi and desert cyanobacteria facilitates biological soil crust formation and soil fertility - Zhou, Xiangjun; Liang, Bin; Zhang, Tian; Xiong, Qiao; Ma, Xiao; Chen, Lanzhou (Frontiers in Microbiology, 2024)
The inoculation of cyanobacteria for enriching soil nutrients and forming biological soil crusts (BSCs) is considered an effective means to restore degraded soil. However, there are limited studies on the application of co-inoculation of fungi and cyanobacteria for degraded soil remediation. In this study, a high exopolysaccharide-secreting fungi Zh2 was isolated from lichen BSCs in Hobq Desert, and co-inoculated with a cyanobacterial strain identified as Phormidium tenue in different proportions to form BSCs on sand during a 35 days incubation period. Results revealed significant differences in crust biomass and soil properties among crusts with different cyanobacterial/fungal inoculation ratios. Microbial biomass, soil nutrient content and enzyme activities in crusts co-inoculated with cyanobacteria and fungi were higher than those inoculated with cyanobacteria and fungi alone. The inoculation of cyanobacteria contributed to the fulvic-like accumulation, and the inoculated fungi significantly increased the humic-like content and soil humification. Redundancy analysis showed that the inoculation of cyanobacteria was positively correlated with the activities of urease and phosphatase, and the content of fulvic-like. Meanwhile, the inoculation of fungi was positively correlated with the contents of total carbon, total nitrogen and humic-like, the activities of catalase and sucrase. Cyanobacteria and fungi play distinct roles in improving soil fertility and accumulating dissolved organic matter. This study provides new insights into the effects of cyanobacteria and fungi inoculations on the formation and development of cyanobacterial-fungus complex crusts, offering a novel method for accelerating induced crust formation on the surface of sand.